ANALISIS YURIDIS POLITIK HUKUM TATA NEGARA (Suatu Kajian Tentang Pancasila dan Kebhinnekaan Sebagai Kekuatan Negara Kesatuan Republik Indonesia) - Rudi Santoso; Agus Hermanto (Postgraduate State Islamic Institute (IAIN) Metro, 2020)
The many threats of radicalization in the middle of society, the demonstration actions that often ask for the application of certain ideologies within the state of Indonesia, the conflict between ethnic, religious, racial and custom makes the tranquility of Bhinneka Tunggal Ika society to be threatened and the erosion of values Pancasila among the younger generation that endanger the survival of the Indonesian nation.The problem of this research is how the Political Law of the State in the concept and context of Pancasila and Diversity in defending the Unitary State of the Republic of Indonesia and How the Strength of the Unitary State of the Republic of Indonesia Based on Pancasila and Unity in Diversity and How Radicalism and Threat Against the Unity of the Unitary Republic State Indonesia.This research uses normative juridical approach method, then data collection procedure is done by literature study, data processing procedure is done by data classification, data inventory, systematization of data, and data analysis is done by qualitative method.The result of the research, the politics of constitutional law in the concept and context of Pancasila and Diversity in defending the Unitary State of the Republic of Indonesia in accordance with the nationalist ideology set forth in the 1945 Constitution, the power of the Unitary State of the Republic of Indonesia based on Pancasila and Diversity is based on the strength of local wisdom from all elements of the nation Indonesia, radicalism and threats to the unity of the Unitary State of the Republic of Indonesia through the strengthening of national insight among the younger generation and the people and leaders of the nation and state apparatus.Suggestion in this research, expected to government can reinforce study of nationality and education of Pancasila and Diversity, to Indonesian society.